Spectrum Licensing and Flexible Beauty Contest Designs - Madden, Gary; Bohlin, Erik; Tran, Thien (Wiley-Blackwell Publishing Ltd., 2013)
McMillan’s (1995) ‘flexibility’ proposition suggests a testable hypothesis about beauty contests spectrum assignments. Such flexibility purportedly allows regulators to pursue social welfare (network deployment) goals. A separate argument is that more competitive beauty contests enhance the probability of assignment. The study concludes that regulators do indeed focus on societal (network deployment) welfare goals. Initially, consideration is given in the immediate term where licenses are awarded based on operator aftermarket commitments. Subsequently, spectrum package attributes and financial performance obligations, specified in the tender documents, come into play to support the networks spread more widely through the population in a timely manner. Finally, the econometric results suggest that more competitive beauty contests enhance the probability of assignment.